ANTI-ANAEMIC POTENTIAL OF METHANOLIC LEAF EXTRACT OF MUCUNA PRURIENS ON PHENYLHYDRAZINE (PHZ) INDUCED ANAEMIC ALBINO WISTAR RATS - Naman, Kasang; Oseni, Habibat; Enoh, Emmanuel (FUDMA JOURNAL OF SCIENCES, 2020)
The antianaemic potential of methanolic leaf extracts of Mucuna pruriens was investigated using phenylhydrazine (PHZ) induced anaemic albino Wistar rats.  Fifteen rats used for the study were randomized into five experimental groups. To induced anaemia, the rats (except the normal control, Group E), received 60 mg/kg of the haemolytic agent Phenylhydrazine intraperitoneally (i.p) for two consecutive days. Anaemic Wistar rats in groups A and B received a daily oral dose of 500 and 250 mg/kg of the methanolic leaf extract of Mucuna pruriens. Nweze et al. (2016) had reported a median lethal dose greater than 5000 mg/kg for the methanol leaf extract of Mucuna pruriens. Groups C and D received Vitamin B12 (10 mg/kg) and normal saline (1 ml/kg), respectively. Normal control rats also received normal saline (1 ml/kg). Extract or normal saline was administered per os (p.o) while vitamin B12 was administered i.p. for a duration of 21 days. Packed cell volume (PCV) and haemoglobin concentration were determined weekly for three weeks. The result of the study indicated that both the methanolic leaf extract of Mucuna pruriens and Vitamin B12 significantly (p < 0.05) increased the packed cell volume and haemoglobin concentrations in treated rats compared to the negative control group of rats. This indicated that the methanolic leaf extract of Mucuna pruriens has anti-anaemic properties and could be utilized in the management of anaemia